Synthesis and anti-human immunodeficiency virus activity of substituted ( o,o-difluorophenyl)-linked-pyrimidines as potent non-nucleoside reverse transcriptase inhibitors - Čechová, Lucie; Dejmek, Milan; Baszczyňski, Ondřej; Šaman, David; Gao, Liping; Hu, Eric; Stepan, George; Jansa, Petr; Janeba, Zlatko; Šimon, Petr (Antiviral chemistry & chemotherapy, 2019)
With the worldwide number of human immunodeficiency virus positive patients stagnant and the increasing emergence of viral strains resistant to current treatment, the development of novel anti-human immunodeficiency virus drug candidates is a perpetual quest of medicinal chemists. Herein, we report a novel group of diarylpyrimidines, non-nucleoside reverse transcriptase inhibitors, which represents an important class of current anti-human immunodeficiency virus therapy. Series of diarylpyrimidines containing o, o-difluorophenyl (A-arm), 4-cyanophenylamino (B-arm), and a small substituent (e.g. NH2, OMe) at positions 2, 4, and 6 of the pyrimidine ring were prepared. The A-arm was modified in the para position (F or OMe) and linked to the central pyrimidine core with a variable spacer (CO, O, NH). Antiviral activities of 20 compounds were measured against wild type human immunodeficiency virus-1 and mutant reverse transcriptase strains (K103N, Y181C) using a cytoprotection assay. To the most promising structural motives belong the o, o-difluoro- p-methoxy A-arm in position 4, and the amino group in position 6 of pyrimidine. Single digit nanomolar activities with no significant toxicity (CC50 > 17,000 nM) were found for compounds 35 (EC50 = 2 nM), 37 (EC50 = 3 nM), and 13 (EC50 = 4 nM) having O, NH, and CO linkers, respectively.
Keywords: Microbial Sensitivity Tests; Models, Molecular; Humans; Anti-HIV Agents; pyrimidiny; HIV Reverse Transcriptase; Reverse Transcriptase Inhibitors; HIV reverzní transkriptasa; krystalografie rentgenová; mikrobiální testy citlivosti; Crystallography, X-Ray; lidé; magnetická rezonanční spektroskopie s uhlíkem 13C; molekulární modely; non-nucleoside reverse transcriptase inhibitor; molekulární struktura; vyvíjení léků; inhibitory reverzní transkriptasy; Molecular Structure; buněčné linie; Cell Line; protonová magnetická rezonanční spektroskopie; látky proti HIV; rilpivirine; human immunodeficiency virus; etravirine; Proton Magnetic Resonance Spectroscopy; Pyrimidines; HIV-1; Drug Development; Diarylpyrimidine; Carbon-13 Magnetic Resonance Spectroscopy